TINJAUAN YURIDIS PERLINDUNGAN HAK CIPTA KARYA SENI DIGITAL DALAM BENTUK NON FUNGIBLE TOKEN (NFT) - Vrancesco Jefta; Hulman Panjaitan; Andrew Betlehn (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2024)
The presence of Non-Fungible Tokens (NFTs) provides a unique appeal and empowers artists in unprecedented ways. The weakness in protecting digital copyrights stems from the perception that online art is public property. Thus, raising public awareness about digital copyright protection is crucial. The problem statement of this thesis is: How is the legal protection of digital art NFTs, and what are the obstacles and challenges in implementing NFT copyright law. This research uses a normative legal approach, utilizing legislative and library research. Secondary data includes primary legal materials such as the Civil Code, Law Number 28 of 2014, and Law Number 1 of 2024. Secondary legal materials are sourced from books and other literature, and tertiary legal materials include dictionaries. The collected materials are compiled and analyzed. The research concludes that repressive copyright protection is regulated in the Copyright Law. Preventive measures include public awareness campaigns and applying watermarks to artworks to prevent theft. Besides the Indonesian government, NFT marketplaceoperators also protect copyright by issuing warnings and imposing sanctions like account blocking